(untitled) (Baghdad Science Journal, 2007)
A theoretical study by using computer model is presented to study the energy characteristics of the vibrational – rotational levels as a function of the vibrational and rotational quantum number, respectively. The calculations were based on the basis of a multilevel model taking into account the non-equilibrium population of the rotational levels. The computational investigation has been performed to examine the vibrational-rotational characteristics of some hydrogen halides chemical laser molecules. This program takes into account the various molecules of chemical lasers such as, Hydrogen Fluoride (HF), Deuterium Fluoride (DF), Hydrogen Chloride (HCl), and Deuterium Chloride (DCl). The practical difficulties associated with this type of lasers suggested that alternative route might be quite useful. Thus particular attention was paid to the development of computer program to investigate various energy characteristics. Comparison of the calculated results for different molecules shows that the highest values for the HF molecule probably due to their higher constants in comparison with the other molecules.